2015
DOI: 10.1111/mmi.12906
|View full text |Cite
|
Sign up to set email alerts
|

Roles for both FtsA and the FtsBLQ subcomplex in FtsN‐stimulated cell constriction in Escherichia coli

Abstract: SUMMARY Escherichia coli FtsN is a bitopic membrane protein that is essential for triggering active cell constriction. A small periplasmic subdomain (EFtsN) is required and sufficient for function, but its mechanism of action is unclear. We isolated extragenic EFtsN*-suppressing mutations that restore division in cells producing otherwise non-functional variants of FtsN. These mapped to the IC domain of FtsA in the cytoplasm and to small subdomains of the FtsB and FtsL proteins in the periplasm. All FtsB and F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
383
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 174 publications
(410 citation statements)
references
References 104 publications
(168 reference statements)
23
383
3
1
Order By: Relevance
“…Because FtsN activates the divisome for constriction, whereas FtsE D162N X allows divisome assembly but not cell constriction, it suggests they have opposing activities in the divisome. Because both the cytoplasmic ( N FtsN) and the essential ( E FtsN) domains of FtsN play important roles in activating the divisome (24), we tested their role in counteracting FtsE D162N X by using FtsN mutants with mutations that inactivate N FtsN (FtsN D5N ) or E FtsN (FtsN WYAA ) (24,25). A Western blot showed that these mutants were expressed at the same level as wild-type FtsN (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Because FtsN activates the divisome for constriction, whereas FtsE D162N X allows divisome assembly but not cell constriction, it suggests they have opposing activities in the divisome. Because both the cytoplasmic ( N FtsN) and the essential ( E FtsN) domains of FtsN play important roles in activating the divisome (24), we tested their role in counteracting FtsE D162N X by using FtsN mutants with mutations that inactivate N FtsN (FtsN D5N ) or E FtsN (FtsN WYAA ) (24,25). A Western blot showed that these mutants were expressed at the same level as wild-type FtsN (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Interaction between N FtsN and FtsA brings E FtsN to the division site so that these two signals synergize to derepress the FtsQLB complex and activate septal PG synthesis (Fig. 1B) (24,29,30). As new PG is synthesized, amidases regulated by FtsEX generate denuded glycan chains, resulting in more recruitment of FtsN by binding of S FtsN and forming a positive feedback loop (12).…”
Section: Significancementioning
confidence: 99%
See 3 more Smart Citations